Feasibility of using ultrasonic-based prediction for hydrogen embrittlement susceptibility of high-strength heat-resistant steel 2.25Cr-1Mo-0.25V. (15th June 2022) - Ye, Dongdong; Yin, Changdong; Xu, Zhou; Chen, Jianjun; Wu, Yiwen; Pan, Jiabao; Zeng, Guiling; Xu, Huachao; Li, Rui
Highlights: Quantifying the degree of mechanical property degradation for the steel after hydrogenation using HE index. A nondestructive testing method based on pulse-echo ultrasonic measurement technique to estimate HE was proposed. SWT-based signal reconstruction technique was used to improve the measurement accuracy of ultrasonic echo signal. The feasibility of the method was verified by constructing ultrasonic characteristic parameters sensitive to HE. Abstract: Nondestructive evaluation for the mechanical properties loss of equipment materials serviced in the hydrogen environment is particularly vital for monitoring the equipment operating conditions. In this study, the quantitative relationship between the introduced hydrogen content and the mechanical property degradation of 2.25Cr-1Mo-0.25V steel was investigated using electrochemical hydrogen charging technique and tensile testing, and a nondestructive testing method based on pulse-echo ultrasonic measurement technique, combined with the results of mechanical assessment for hydrogen embrittlement (HE) susceptibility, was proposed to indirectly estimate the degree of hydrogen-induced plasticity loss of the steel. Moreover, signal reconstruction technique was also used to improve the measurement accuracy of ultrasonic echo signal. The results of the study showed that hydrogen present in the metal lattice intensifies the energy attenuation of ultrasonic echo, verifying the feasibility and validity of the measurement method in the effective online prediction of HE susceptibility of the tested steel.